Implementasi Metode Asosiasi Transaksi Penjualan Menggunakan Algoritma Apriori pada Studi Kasus Toko Sembako Ibu Siti - Wieko, Wieko; Wahyudi, Tri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This research aims to implement the transaction association method using the Apriori Algorithm in the case study of Ibu Siti's Grocery Store. In a retail environment, understanding customer purchasing patterns is crucial for effective marketing strategies and product arrangement. The Apriori Algorithm was chosen for its capability to discover association rules from large transaction datasets, which will yield valuable information regarding relationships between sales items. The implementation process includes data pre-processing, candidate itemset generation, and the calculation of support, confidence, and lift to extract significant association rules. The results of this research are expected to provide strategic recommendations for Ibu Siti's Grocery Store in arranging product layouts, planning package promotions, and managing product inventory more efficiently. Thus, the application of this algorithm is expected to increase the store's profit and competitiveness.